Futuros posibles. Transformación material a partir de plantas invasoras - Álvarez Durán, Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
From the water lily (EICHORNIA CRASSIPESSE), an invasive plant that generates multiple ecosystem problems around the world and considered one of the 100 most harmful species, experiments were carried out to take advantage of it for new materials. To achieve this, a methodological appropriation created from Design Thinking with hybridization of the Material Driven Design Method was used. It was accompanied by an experimental protocol of three stages called exploratory, material and functional, limited to the generation of two material lines, one with qualities of flexibility and another of rigidity. The result generated a flexible material that was generated from encapsulating the root of the water lily in collagen and vegetable glycerin, which has visual and tactile characteristics like leather, as well as another with rigid characteristics made from the dried water lilies of the water lily accompanied by starch as a natural binder, with it, bio-based agglomerates with qualities for compression molding can be generated. Both materials have various benefits that make them suitable for application, especially in areas of moderate use. However, the development and speculations of the bio-composite derived from better results and having a better capacity to take advantage of the natural and underutilized abundance of an invasive plant to attack the infection of water bodies at the same time as generating more friendly material options with environment.

A partir del lirio acuático (EICHORNIA CRASSIPESSE), planta invasora que genera múltiples problemas ecosistémicos alrededor del mundo y considerada una de las 100 especies más dañinas, se realizaron experimentos con la finalidad de aprovecharla para nuevas materialidades. Para lograrlo se utilizó una apropiación metodológica creada a partir de Design Thinking con hibridación del Material Driven Desing Method. Se acompaño de un protocolo experimental de tres etapas denominadas como exploratorio, material y funcional, acotado a la generación de dos líneas materiales, una con cualidades de flexibilidad y otra de rigidez. El resultado generó un material flexible que se generó a partir de encapsular la raíz del lirio acuático en colágeno y glicerina vegetal, el cual tiene características visuales y táctiles semejantes a un cuero, así mismo otro con características rígidas elaborado a partir de los nenúfares secos del lirio acuático acompañado de almidón como aglutinante natural, con él, se puede generar aglomerados bio-basado con cualidades para moldeo sometido a compresión. Ambos materiales cuentan con diversas bondades que los hacen aptos de aplicación, sobre todo en ámbitos de uso moderado. Sin embargo, se profundizó el desarrollo y especulaciones al bio-compuesto derivado de mejores resultados y tener mejor capacidad de aprovechar la abundancia natural y subutilizada de una planta invasora para ataca la infección de cuerpos de agua a la par de generar opciones materiales más amigables con el medio ambiente.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2022-0235; Biomaterial; Lirio acuático; Diseño experimental; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6689